PRODAN dual emission feature to monitor BHDC interfacial properties changes with the external organic solvent composition - Agazzi, Federico Martin (2013)
We have investigated the water/benzyl-n-hexadecyldimethylammonium chloride (BHDC)/n-heptane:benzene reverse micelles (RMs) interfaces properties using 6-propionyl- 2-(N,N-dimethyl)aminonaphthalene, PRODAN, as molecular probe. We have used absorption and emission (steady-state and time-resolved) spectroscopy of PRODAN to monitor the changes in the RMs interface functionalities upon changing the external organic solvent blend. We demonstrate that PRODAN is a useful probe to investigate how the external solvent composition affects the micelle interface properties. Our results show that changes in the organic solvent composition in water/BHDC/n-heptane:benzene RMs have a dramatic effect on the photophysics of PRODAN. Thus, increasing the aliphatic solvent content over the aromatic one produces PRODAN partition and PRODAN intramolecular electron transfer (ICT) processes. Additionally, the water presence in these RMs makes the PRODAN ICT process favored with the consequent decreases in the LE emission intensity and a better definition of the charge transfer (CT) band. All this evidence suggests that the benzene molecules are expelled out of the interface, and the water−BHDC interactions are stronger with more presence of water molecules in the polar part of the interface. Thus, we demonstrate that a simple change in the composition of the external phase promotes remarkable changes in the RMs interface. Finally, the results obtained with PRODAN together with those reported in a previous work in our lab reveal that the external phase is important when trying to control the properties of RMs interface. It should be noted that the external phase itself, besides the surfactant and the polar solvent sequestrated, is a very important control variable that can play a key role if we consider smart application of these RMs systems.